Preterm birth and subsequent timing of pubertal growth, menarche, and voice break - Suikkanen Julia; Nurhonen Markku; Cole Tim J.; Paalanne Marika; Matinolli Hanna-Maria; Tikanmäki Marjaana; Vääräsmaki Marja; Järvelin Marjo-Riitta; Hovi Petteri; Kajantie Eero (SPRINGER NATURE, 2022)
Background: We evaluated pubertal growth and pubertal timing of participants born preterm compared to those born at term.
Methods: In the ESTER Preterm Birth Study, we collected growth data and measured final height of men/women born very or moderately preterm (<34 gestational weeks, n = 52/55), late preterm (34-<37 weeks, 94/106), and term (>= 37 weeks, 131/151), resulting in median 9 measurements at >= 6 years. Timing of menarche or voice break was self-reported. Peak height velocity (PHV, cm/year) and age at PHV (years) were compared with SuperImposition by Translation And Rotation (SITAR) model (sexes separately).
Results: Age at PHV (years) and PHV (cm/year) were similar in all gestational age groups. Compared to term controls, insignificant differences in age at PHV were 0.1 (95% CI: -0.2 to 0.4) years/0.2 (-0.1 to 0.4) for very or moderately/late preterm born men and -0.0 (-0.3 to 0.3)/-0.0 (-0.3 to 0.2) for women, respectively. Being born small for gestational age was not associated with pubertal growth. Age at menarche or voice break was similar in all the gestational age groups.
Conclusions: Timing of pubertal growth and age at menarche or voice break were similar in participants born preterm and at term. Impact Pubertal growth and pubertal timing were similar in preterm and term participants in a relatively large cohort with a wide range of gestational ages. Previous literature indicates that small for gestational age is a risk for early puberty in term born children. This was not shown in preterm children. While our study had limited power for children born very preterm, all children born preterm were not at increased risk for early puberty.